Peran Guru Sekolah Dasar dalam Menumbuhkan Jiwa Kewirausahaan Anak di Masa Pandemi Covid-19 - Ana Rochiyanti; Imam Mawardi (Prosiding University Research Colloquium, 2021)
This research is a qualitative descriptive research, by providing an overview of thecultivation of an entrepreneurial spirit in SD Negeri 1 Purwojati. The research techniquewas carried out in two ways, namely interview and documentation techniques. While thedata analysis technique with descriptive analysis. The result showed that the teachers ofSD Negeri 1 Purwojati instilled an entrepreneurial spirit by incorporatingentrepreneurial values into learning and providing some skills to make useful objectsfrom objects aroundthem. The entrepreneurial values that are instilled are: 10innovative; 2) hard work; 3) leadership; 4) tenacious; 5) dare to take risks; 6)commitment; 7) reality ; and 8) communicative